Naturen 1916 Roald Amundsens sydpolsfærd og dens videnskabelige resultater (Naturen, 2016)
Efterat kaptein James Ross i 1841 hadde opdaget det sydpolare eller antarktiske fastland og den store isbarriere under sin seilas i det hav som efter ham har faat navn av Ross-Havet, blev den øvrige del av dette fastland fremdeles ukjendt indtil 1898. Fra dette aar av har en række ekspeditioner med større og mindre held forsøkt at finde beliggenheten av det antarktiske fastlands kyster, og av disse har nogen opnaadd at trænge ind i det indre, endog like til sydpolen. Imidlertid er der endnu store strækninger hvor havisen har stængt seilasen og gjort det umulig at naa ind til det faste land.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; historie; oppdagelsesreiser; vitenskap

Delivering 21st century Antarctic and Southern Ocean science - Kennicutt, Mahlon C I I; Kim, Yeadong; Rogan-Finnemore, Michelle; Anandakrishnan, Sridhar; Chown, Steven L; Colwell, Steven (Antarctic Science, 2016)
The Antarctic Roadmap Challenges (ARC) project identified critical requirements to deliver high priority Antarctic research in the 21st century. The ARC project addressed the challenges of enabling technologies, facilitating access, providing logistics and infrastructure, and capitalizing on international co-operation. Technological requirements include: i) innovative automated in situ observing systems, sensors and interoperable platforms (including power demands), ii) realistic and holistic numerical models, iii) enhanced remote sensing and sensors, iv) expanded sample collection and retrieval technologies, and v) greater cyber-infrastructure to process ‘big data’ collection, transmission and analyses while promoting data accessibility. These technologies must be widely available, performance and reliability must be improved and technologies used elsewhere must be applied to the Antarctic. Considerable Antarctic research is field-based, making access to vital geographical targets essential. Future research will require continent- and ocean-wide environmentally responsible access to coastal and interior Antarctica and the Southern Ocean. Year-round access is indispensable. The cost of future Antarctic science is great but there are opportunities for all to participate commensurate with national resources, expertise and interests. The scope of future Antarctic research will necessitate enhanced and inventive interdisciplinary and international collaborations. The full promise of Antarctic science will only be realized if nations act together.
Keywords: Antarktis; forskning; vitenskap